Trends and Determinants of Underweight among Under-Five Children in Ethiopia: Data from EDHS - Haile Mekonnen Fenta; Lijalem Melie Tesfaw; Muluwerk Ayele Derebe (Hindawi Limited, 2020)
Background and Aims. Malnutrition among under-five children is one of the major causes of death in low-income countries. Accordingly, health sectors in developing countries are providing renewed attention to the status of children's nutrition. This study sought to explore the trends and identify the determinants of underweight Ethiopian under-five children across time. Methods. The data in the study was obtained from the 2000, 2005, 2011, and 2016 Ethiopian Demographic and Health Surveys (EDHS). The study involved 27564 under-five children across Ethiopian regions. The status of underweight is determined using weight for age. This anthropometric index has been categorized as "underweight" (Z-score less than -2) and "not underweight" (Z-score greater or equal to -2). Logistic regression was used for each survey to detect significant determinants of underweight, while multivariate decomposition was used to determine the trends and identified the child, maternal, and household characteristics that are associated with underweight. Result. The survey in 2000, 2005, 2011, and 2016 showed that 41, 33, 29, and 24% of sampled under-five children were underweight, respectively, and after adjusting for confounders, children were more likely to be underweight if they were male (OR=1.16, 95%CI=1.02, 1.33) in 2016 EDHS. Children whose mother's age is below 20 (OR=5.75, 95%CI=1.44, 23.1)) were more likely to be underweight compared with children whose mother's age is above 45. Children whose mothers had no education and primary education only (OR=1.65, 95% CI 1.05, 2.59 and OR=1.43, 95% CI 1.15, 1.78, respectively) were more likely underweight compared to children whose mothers had higher education. Conclusion. Children's age, birth weight, mother's education status, and children's gender were the most common significant factors of underweight. The prevalence of underweight among under-five children declined over time which leads to an achievement in terms of meeting millennium development goals and nutritional targets. Government and concerned stakeholders should work to maintain this achievement for further reduction of underweight among under-five children.